Penetapan Kadar Aspartam Pada Minuman Berenergi “X” Serbuk Dengan Metode Kromatografi Cair Kinerja Tinggi - Abeiasa, M. Saka; Humaira, Vilma; Yuza, Novendra (Jurnal Medisains Kesehatan, 2022)
Energy drinks are currently being consumed by more and more people, which unwittingly contain artificial sweeteners such as aspartame. Aspartame can cause various disorders in the body if consumed in excess of 40 mg/kg body weight. The High Performance Liquid Chromatography (HPLC) method is often used to determine aspartame levels in food or beverages. This study aims to determine the validation of the aspartame aspartame determination method and to determine the aspartame content in energy drink "X" by HPLC. The HPLC system used includes a Lichrospher 100 RP-18 column, particle size 5μm, column length 125 mm, flow rate = 1.0 ml/min, loop volume = 20μl, and column temperature = 30oC. The mobile phase selected was ammonium acetate: methanol (70:30). The degree of resolution obtained is in the range of 1.68-1.89, detection limit = 1.4790, quantity limit = 3.7802, Vxo = 1.17%, % recovery = 100.80%-118.98%, and The aspartame examined was in the range of 0.90%-1.22% (35.15-49.47 mg). This study concluded that the aspartame aspartame assay analysis method using HPLC met the method validation requirements, which included selectivity, linearity, detection limit, quantity limit, accuracy, and precision. Aspartame levels in energy drink "X" is quite high and exceeds the standard daily intake allowed